Analisis Pengaruh Variabel Makroekonomi Terhadap Penerimaan Zakat Pada Baznas Periode 2016-2021 - Hikmah Lailatul Mukarromah; Asyari Hasan (ITB AAS INDONESIA Surakarta, 2023)
Every Muslim who fulfills the terms and conditions of Islamic law is obliged to pay zakat because zakat is one of the pillars of Islam. Instrument that can reduce poverty is zakat. The collection of zakat in Indonesia very potential, but this is not in line with the realization of the total collection of national zakat funds in 2019 which only reached 0.04 percent of its total potential of IDR 233.8 trillion. The purpose of this study is to analyze the effect and response of macroeconomic variable shocks to zakat collects and to analyze the contribution of each macroeconomic variable to zakat receipts at BAZNAS using the Vector Error Correction Model (VECM) method. The results showed that the IPI and Exchange Rate variables responded positively to zakat receipts, while the Inflation, Money Supply and BI 7-Day Repo Rate variables responded negatively to zakat receipts. FEVD results show that the biggest contribution to the receipt of zakat is the exchange rate and industrial production index among other variables used.